Fault-tolerant synchronization for nonlinear switching systems with time-varying delay. (February 2017) - Liu, Xinzhi; Wu, Cong
Abstract: This paper studies fault-tolerant synchronization for nonlinear switching systems with time-varying delay using impulsive feedback control. Both faults and disturbances in the drive system are taken into account. In order to deal with these faults, we adopt an input–output fault model by which faults are regarded as outputs corresponding to inputs that approach zero as time goes to infinity. Based on this principle, by using an observer-based fault estimator with output feedback controllers and impulsive state feedback controllers, we design a fault-tolerant synchronization scheme, by which the synchronization can be eventually reached no matter whether there are faults, disturbances in the drive system or not. The problem of design is formulated so as to find control gain matrices in the controllers such that the trivial solution of the error system is globally attractive and the L 2 norm of the error between fault and its estimation is bounded by that of the vector consisting of the fault input and disturbance. Several criteria for this problem are derived in terms of linear matrix inequalities. Finally, a hybrid Chua's circuit is used to illustrate the effectiveness of the proposed method.